Computer Vision-Inspired Design of Children's Medical Products - Zhenyu, Gao; Mohd Najib, Abdullah Sani (U-turn Press LLC, 2024)
The purpose of this study is to optimize the CAD (computer-aided design) of children's medical products by using computer vision and DM (Data mining) technology. This article explores the application potential of computer vision and DM technology in the design of children's medical products. This article constructs a CAD design model of children's medical products combining computer vision and DM technology and verifies the feasibility and effectiveness of the CAD design model through simulation experiments. Simulation experiments and comparative experiments are carried out in this article to verify the performance of the CAD design model. The results show that the design scheme generated based on the CAD design model is significantly better than the traditional design method in personalization, accuracy, and efficiency. In addition, the user survey results also show that the medical products generated by using CAD design models can better meet the specific needs and preferences of children and improve user satisfaction with products. It provides a new and efficient method and technical support for the design of children's medical products.